2011
DOI: 10.5194/nhess-11-771-2011
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid neural networks in rainfall-inundation forecasting based on a synthetic potential inundation database

Abstract: Abstract. This study attempts to achieve real-time rainfallinundation forecasting in lowland regions, based on a synthetic potential inundation database. With the principal component analysis and a feed-forward neural network, a rainfall-inundation hybrid neural network (RiHNN) is proposed to forecast 1-h-ahead inundation depth as hydrographs at specific representative locations using spatial rainfall intensities and accumulations. A systematic procedure is presented to construct the RiHNN, which combines the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…On the other hand, when the test case is removed from the training set, the prediction is still better than the original TRCM prediction, in that the amount of rainfall as well as the multiple peak of rainfall is predicted. The performances of original TRCM prediction and TRCM prediction with ANNSME are further evaluated by root mean square error (RMSE), error of cumulative rainfall (ECR), and error of the time for peak to arrive (ET p ) in Table 5 (Pan et al 2011). We found that the RMSE and ECR are improved through TRCM prediction with ANNSME in all cases except the extreme rainfall case at ALiShan in Typhoon Morakot.…”
Section: The Annsme Resultsmentioning
confidence: 92%
“…On the other hand, when the test case is removed from the training set, the prediction is still better than the original TRCM prediction, in that the amount of rainfall as well as the multiple peak of rainfall is predicted. The performances of original TRCM prediction and TRCM prediction with ANNSME are further evaluated by root mean square error (RMSE), error of cumulative rainfall (ECR), and error of the time for peak to arrive (ET p ) in Table 5 (Pan et al 2011). We found that the RMSE and ECR are improved through TRCM prediction with ANNSME in all cases except the extreme rainfall case at ALiShan in Typhoon Morakot.…”
Section: The Annsme Resultsmentioning
confidence: 92%
“…Leedal et al (2010) proposed twodimensional (2-D) real-time probabilistic inundation maps based on a modified Kalman filter model coupled into 2-D hydrodynamic model to compute the maximum multistepahead inundation extent. Pan et al (2011) used hybrid ANNs in rainfall-inundation forecasting to estimate 1-h-ahead inundation depths.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial neural networks (ANNs) are a kind of information processing system with great flexib ility in modeling nonlinear systems. As to inundation forecasting, applications of NNs have been presented (Chang et al [3]; Pan et al [7]). The ASCE Task Co mmittee [1,2] and Maier and Dandy [6] have presented comprehensive reviews of the applications of ANNs in hydrology.…”
Section: Introductionmentioning
confidence: 99%